ВІДПОВІДАЛЬНІСТЬ ЯК ВАЖЛИВИЙ ПОКАЗНИК ВИХОВАНОСТІ ОСОБИСТОСТІ ДИТИНИ (Педагогіка вищої та середньої школи, 2007)
The notion of the responsibility of the personis opened in the article, peculiarities of its development in preschool age is considered; the main features of definitions of responsibility of children in preschool age are found.